Parallel Changes in Harvey-Bradshaw Index, TNFα, and Intestinal Fatty Acid Binding Protein in Response to Infliximab in Crohn’s Disease - Anas Kh. Al-Saffar; Carl Hampus Meijer; Venkata Ram Gannavarapu; Gustav Hall; Yichen Li; Hetzel O. Diaz Tartera; Mikael Lördal; Tryggve Ljung; Per M. Hellström; Dominic-Luc Webb (Gastroenterology Research and Practice, 2017)
Intestinal fatty acid binding protein (I-FABP) indicates barrier integrity. Aims: determine if I-FABP is elevated in active Crohn’s disease (CD) and if I-FABP parallels anti-TNFα antibody (infliximab) induced lowering of TNFα and Harvey-Bradshaw Index (HBI) as potential indicator of mucosal healing. I-FABP distribution along human gut was determined. Serum from 10 CD patients collected during first three consecutive infliximab treatments with matched pretreatment and follow-up samples one week after each treatment and corresponding HBI data were analyzed. I-FABP reference interval was established from 31 healthy subjects with normal gut permeability. I-FABP and TNFα were measured by ELISA; CRP was measured by nephelometry. Healthy tissue was used for I-FABP immunohistochemistry. Pretreatment CD patient TNFα was 1.6-fold higher than in-house reference interval, while I-FABP was 2.5-fold higher, which lowered at follow-ups. Combining all 30 infusion/follow-up pairs also revealed changes in I-FABP. HBI followed this pattern; CRP declined gradually. I-FABP was expressed in epithelium of stomach, jejunum, ileum, and colon, with the highest expression in jejunum and ileum. I-FABP is elevated in active CD with a magnitude comparable to TNFα. Parallel infliximab effects on TNFα, HBI, and I-FABP were found. I-FABP may be useful as an intestine selective prognostic marker in CD.